(untitled) (Research, Society and Development, 2021)
The present work aims to evaluate a direct exposure solar drying system that uses a desiccant unit, is of low cost, easy operation, high efficiency and accessible to family farmers for drying pineapple, under the meteorological conditions of the semiarid region. northeastern. As a methodology, a comparison was made between two drying systems, one with a desiccant unit containing silica gel and the other without a desiccant unit, where the drying time of pineapple and the thermal efficiency of the equipment were evaluated. The pineapple used had a moisture content on a wet basis of 86.22%. The main experimental results showed that the ambient air passing through the desiccant unit had more favorable conditions for carrying out the drying process, namely, higher temperature and lower relative humidity. Thus, there was a 60 min reduction in the drying time required for the pineapple to reach a moisture content on a wet basis of 25% compared to the drying system without a desiccant unit. The average of the thermal yields of the drying systems without desiccant unit and with desiccant unit were, respectively, 39.15% and 39.76%. In conclusion, it is possible to state that the operation of the drying systems was carried out without the need for highly complex actions, which proves its ease of operation, making it an appropriate technology for insertion in family farming.